Analisis Campur Kode dalam Film “Cinta Subuh” dan Pemanfaatannya Sebagai Media Pembelajaran Teks Drama di SMA Kelas XI - Dewi, Fitriyani; Nuraini, Cut; Huri, Daman (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to describe the form of code-mixing speech that occurs in the film Cinta Subuh by Ali Farighi by Indra Gunawan, to describe the design or form of TikTok media, and to describe the use of code-mixing analysis in the form of TikTok media in learning dramatic texts in class XI. The method used in this research is a descriptive qualitative research method. Data collection techniques in this research are listening techniques and note-taking techniques. The research results in the film Cinta Subuh found 326 data using 49 speech samples consisting of inward code mixing, 146 data were obtained with 11 samples, 171 data were obtained for outward code mixing with 29 samples and 9 data were obtained for mixed code mixing. with 9 samples. The results of this research will be used as an audiovisual learning medium for drama text material in high school class So it can be concluded that the output or final result of this research is in the form of a TikTok-based audiovisual learning video.